2021
DOI: 10.3390/su132212805
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Education in the Context of COVID-19: Study of the Social Perception and Well-Being of Students at the Faculty of Engineering in Sibiu, Romania

Abstract: The COVID-19 pandemic has had global effects on all industries and on people around the world. The COVID-19 pandemic has had repercussions both politically and economically, as well as on society and the individual, i.e., on the human psyche. Although the effects on the human psyche have been highlighted in research, the well-being of the individual in correlation with social perception have not been addressed in this context but in different situations. The review of the relevant literature has also identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…There is also a need for the Amazonian institution to develop qualification programs for its professors to use virtual tools in the educational process, since, apparently, this may be a trend in the future and its professors need to adapt to this new work dynamic. As also shown in the research by Cioca and Bratu [59], the pedagogical performance of students reduced during online classes, and clear criticisms regarding the performance of professors when teaching online classes emerged, thus demonstrating the importance of implementing educational policies that can minimize these problems in the future.…”
Section: Discussionmentioning
confidence: 81%
“…There is also a need for the Amazonian institution to develop qualification programs for its professors to use virtual tools in the educational process, since, apparently, this may be a trend in the future and its professors need to adapt to this new work dynamic. As also shown in the research by Cioca and Bratu [59], the pedagogical performance of students reduced during online classes, and clear criticisms regarding the performance of professors when teaching online classes emerged, thus demonstrating the importance of implementing educational policies that can minimize these problems in the future.…”
Section: Discussionmentioning
confidence: 81%
“…The scientific literature shows that higher education institutions through their multiple functions (research, education, and societal impact) are increasingly recognized for their potential to contribute to the necessary transformation of society toward sustainability (Bratu and Ionel Cioca, 2019;Cioca and Bratu, 2021;Probst, 2022). According to Popescu et al (2022), the ecotourism is a form of tourism with rural character which involves the use of local natural resources through tourism activities, with multiple benefits for communities bordering protected areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in Lithuania showed that students experienced high levels of anxiety, depression, and suicidal thoughts [ 19 ]. Another study which involved students in the Faculty of Engineering in Sibiu, Romania integrated elements related to the emotional aspect and the changes that occurred during the lockdown, and identified high variations in stress, anxiety, and tension [ 20 ]. The social dimension is characterized by relational, economic, and professional problems and the transition to adulthood, which are catalytic elements in the process of increasing psycho-affective disorders [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Lithuania showed that students experienced high levels of anxiety, depression, and suicidal thoughts [ 19 ]. Another study which involved students in the Faculty of Engineering in Sibiu, Romania integrated elements related to the emotional aspect and the changes that occurred during the lockdown, and identified high variations in stress, anxiety, and tension [ 20 ].…”
Section: Introductionmentioning
confidence: 99%